2007
DOI: 10.1007/s12026-007-0074-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of platelet CD154 in the modulation in adaptive immunity

Abstract: Platelets' primary role is hemostasis. However, a growing body of research has demonstrated that platelets are integral to the initiation of an inflammatory response and are potent effector cells of the innate immune response. Activated platelets express CD154, a molecule critical to adaptive immune responses, which has been implicated in plateletmediated modulation of innate immune responses and inflammation. Recent studies utilizing CD154 knockout mice extend the role of platelet-derived CD154 to the modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…36 PLT-to-LC regulations were demonstrated in PLTmediated inflammatory responses, [37][38][39] and in the modulation of lymphocytes. 40,41 Conversely, less attention has been paid to LC-to-PLT modulation. Previous studies were mainly focused on the influence of LC on the downstream immune/defense responses elicited by PLTs, 36 while DC-mediated regulation of PLTs in response to engagement of CD14 ϩ LC was not demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…36 PLT-to-LC regulations were demonstrated in PLTmediated inflammatory responses, [37][38][39] and in the modulation of lymphocytes. 40,41 Conversely, less attention has been paid to LC-to-PLT modulation. Previous studies were mainly focused on the influence of LC on the downstream immune/defense responses elicited by PLTs, 36 while DC-mediated regulation of PLTs in response to engagement of CD14 ϩ LC was not demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies that are more recent, demonstrated that platelet-derived vesicles might transport and deliver various molecules among cells (9,143,144). Platelet-derived vesicles also participate in innate (145,146) and adapted (62,147) immunity, in inflammation (148), malignancies (149) and in hematopoietic stem cell engraftment (150). They promote endothelial repair and support angiogenesis (151).…”
Section: Background and Clinical Potentialmentioning
confidence: 99%
“…Both of them are important and necessary response to bacterial infection and contain antimicrobial peptides that act against a broad range of pathogens (Elzey et al, 2005 andFitzgerald et al, 2006) demonstrated that platelets are an integral part of inflammation and can also be potent effector cells of the innate immune response. The platelet (CD154 molecule) has a vital importance to adaptive immune responses, is expressed by activated platelets and has been implicated in platelet-mediated modulation of innate immunity and inflammatory disease states (Elzey et al, 2005, Sprague et al, 2007 Antimicrobial peptides from white blood cells and platelets exert a rapid, potent and direct antimicrobial effect that contributes to limiting the infection. In addition, both of neutrophil and lymphocyte cells increased after one week, although after two weeks only lymphocyte cells increased.…”
Section: Discussionmentioning
confidence: 99%